PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA PETUGAS LAPAS DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA MUARA BELITI KABUPATEN MUSI RAWAS - Nasrullah Nasrullah; Supardi Supardi (Jurnal Interprof, 2017)
This research was conducted at Lembaga Pemasyarakatan Narkotika Klas IIa Muara Beliti Kabupaten Musi Rawas. The purpose of obtaining a clear picture of the Effects of Displin and Motivation on Prison Service Performance. The result of simple linear regression coefficient test of the equation obtained by equation as follows: Y = a + bX (Y = 22,085 + 0,458X1). From the simple linear regression equation the discipline can be explained that the constant value is equal to a = 22,085. While the value of regression variable coefficient of discipline of 0.458 units, Conversely if the value of disciplinary regression fell by one unit, then employee performance is also predicted to decrease by 0.458 units. Therefore it can be concluded that the discipline has a direct relationship to the performance of employees. Based on the result of the correlation coefficient test the correlation coefficient value 0.532 is at the interval coefficient of 0.40 to 0.599 which means the relationship between the discipline variable (X1) and employee performance (Y) shows the relationship is and positive correlation value means correlation or discipline (X1) employee performance (Y) direction. The result of t test above can be explained that the discipline variable (X1) on employee performance shows the value of tcount = 4,785 bigger than ttable value 2.021 with significant level = 0,000 <(α) 0.05, df (n-2) 60 - 2 = 58 is of 2.02.